Genome-wide association analysis and admixture mapping in a Puerto Rican cohort supports an Alzheimer disease risk locus on chromosome 12 - Akgun, Bilcag; Feliciano-Astacio, Briseida E.; Hamilton-Nelson, Kara L.; Scott, Kyle; Rivero, Joe; Adams, Larry D.; Sanchez, Jose J.; Valladares, Glenies S.; Tejada, Sergio; Bussies, Parker L.; Silva-Vergara, Concepcion; Rodriguez, Vanessa C.; et al. (Frontiers in Aging Neuroscience, 2024)
Introduction: Hispanic/Latino populations are underrepresented in Alzheimer Disease (AD) genetic studies. Puerto Ricans (PR), a three-way admixed (European, African, and Amerindian) population is the second-largest Hispanic group in the continental US. We aimed to conduct a genome-wide association study (GWAS) and comprehensive analyses to identify novel AD susceptibility loci and characterize known AD genetic risk loci in the PR population. Material and Methods: Our study included Whole Genome Sequencing (WGS) and phenotype data from 648 PR individuals (345 AD; 303 cognitively unimpaired). We used a generalized linear-mixed model adjusting for sex, age, population substructure, and genetic relationship matrix. To infer local ancestry, we merged the dataset with the HGDP/1000G reference panel. Subsequently, we conducted univariate admixture mapping (AM) analysis. Results: We identified suggestive signals within the SLC38A1 and SCN8A genes on chromosome 12q13. This region overlaps with an area of linkage of AD in previous studies (12q13) in independent data sets further supporting. Univariate African AM analysis identified one suggestive ancestral block (p=7.2x10 -6 ) located in the same region. The ancestry-aware approach showed that this region has both European and African ancestral backgrounds and both contributing to the risk in this region. We also replicated 11 different known AD loci -including APOE-identified in mostly European studies, which is likely due to the high European background of the PR population. Conclusions: PR GWAS and AM analysis identified a suggestive AD risk locus on chromosome 12, which includes the SLC38A1 and SCN8A genes. Our findings demonstrate the importance of designing GWAS and ancestry-aware approaches and including underrepresented populations in genetic studies of AD.